2016
DOI: 10.3329/jasbs.v42i2.46225
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Of The Dynamics Of Coastal Island In Bangladesh Using Geospatial Techniques: Domar Char

Abstract: Erosion and accretion rate are found very high in the estuary of an active delta which can be observed by satellite imageries. According to the multispectral satellite imageries it is found that accretion of Domar Char (a little island belongs to Meghna estuary) was more than 1192 hectares in last 25 years. The study was conducted in five years interval from 1990 to 2015 using spatial analyst extension of ArcGIS. It is revealed that accretion rate is about 208 hectares/year and erosion is about 160 hectares/ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Four multi-spectral spatial resolutions with the fewest clouds of Landsat 7 (ETM) for pre-eruption 2009 and Landsat 7 (OLI) 2013, 2017, and Landsat 8 for 2023 years post-eruption were downloaded. To take advantage of the limited availability of cloud-free pictures, data from the United States Geological Survey (USGS) website were used (Emaran et al, 2016;Hossain et al, 2016). The Plawangan Hill vector boundary and Google Earth images from 2023 were used as additional data (Table 1).…”
Section: Forest Land Cover and Carbon Storage Data Collection And Ima...mentioning
confidence: 99%
“…Four multi-spectral spatial resolutions with the fewest clouds of Landsat 7 (ETM) for pre-eruption 2009 and Landsat 7 (OLI) 2013, 2017, and Landsat 8 for 2023 years post-eruption were downloaded. To take advantage of the limited availability of cloud-free pictures, data from the United States Geological Survey (USGS) website were used (Emaran et al, 2016;Hossain et al, 2016). The Plawangan Hill vector boundary and Google Earth images from 2023 were used as additional data (Table 1).…”
Section: Forest Land Cover and Carbon Storage Data Collection And Ima...mentioning
confidence: 99%
“…The area has a semidiurnal tidal regime and is dynamic, with sediment accretion and erosion constantly reshaping and resizing the islands (Hossain et al 2016). For this reason, the topography of the park is changing too.…”
Section: Study Areamentioning
confidence: 99%
“…); Shibly and Takewaka, 2012;Islam et al, 2013;Sarwar and Woodroffe, 2013;Islam et al, 2016) have been conducted using GIS and remote sensing techniques on morphological changes in the coastal areas of Bangladesh, the studies were limited to deal with the retreat of shorelines. Some studies (Krantz, 1999;BWDB, 2001;Morner, 2010;Rahman et al, 2011;Rahman, 2012;Alam and Uddin, 2013;Ali et at., 2013;Sarker et al, 2013;Taguchi et al, 2013;Brammer, 2014;Hussain et al, 2014a,b;Ghosh et al, 2015;Uddin, 2015;Emran et al, 2016;Hossain et al, 2016) have identified the dynamic nature of coastal lands but these studies have been conducted only for specific coastal islands, sections and zones. For instance, the work of Brammer (2014) identified the dynamic nature of land from the perspectives of past records of rising sea levels, and analysed the general picture of erosion and accretion in the Meghna estuary area with lesser details for the western coastal zone and no analysis for the eastern coastal zone of the country.…”
Section: Introductionmentioning
confidence: 99%